The Principle of Freedom To Make An Aqad In Islamic Law and Its Implementation to Sharia Banking in Indonesia - Purnama, Diantara (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2025)
Aqad is a basic requirement in every transaction. In Islam, some principles must be fulfilled in each process of making ‘aqad, one of which is the principle of freedom to make ‘aqad. This principle guarantees the creation of a balance and equal bargaining between the parties conducting the transactions. Along with the development of ‘aqad in Sharia Banking, the principle of freedom to make ‘aqad is sometimes not fulfilled, which causes an imbalance between the parties involved in the transaction. This study aims to determine the regulation of the principle of freedom to make ‘aqad in Islamic law and how the principle is applied in Sharia Banking. The approach method used in this research is normative juridical, which relies on secondary data consisting of primary, secondary, and tertiary legal materials. The results of this research are that ‘ulama fiqh have different opinions about the limitations of the principle of freedom to make ‘aqad to be included in the terms of the ‘aqad, there are those who allow it and those who don't. The implementation of the freedom to make ‘aqad in terms of making a clause in the ‘aqad of Sharia Banking in Indonesia, the customer is not yet fully able to claim the right of freedom to make ‘aqad because Sharia bank offers standard contracts to its customers and the customer only has the option to take it or leave it.